USABILITY ASSESSMENT OF THE LEADERSHIP MODEL FOR ORANG ASLI SCHOOLS IN MALAYSIA USING THE FUZZY DELPHI METHOD (FDM) - Mohd Sahrul Hisam Mohamed Salleh; Ahmad Zabidi Abdul Razak (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This research examines the effectiveness of specific leadership model elements designed for school leaders within the Indigenous Orang Asli community in Malaysia, utilizing the Fuzzy Delphi Method (FDM). The panel of experts consisted of 13 headteachers from Orang Asli national schools. The study addresses the primary leadership and educational challenges faced by the Orang Asli, considering their distinct cultural, geographical, and socioeconomic circumstances, which require a unique approach different from conventional schools. This evaluation is part of the third stage in the Design and Development Research (DDR) framework, employing a structured approach to test the usability and relevance of four primary leadership components: intrapersonal leadership, holistic leadership, cultural leadership, and collaborative leadership. The results show a high level of appropriateness for all components, as evidenced by a threshold (d) value of ≤ 0.2, a fuzzy score of ≥ 0.5, and a consensus percentage of ≥ 75%. Additionally, the study highlights the necessity for an inclusive and comprehensive leadership strategy in Indigenous education that honors the cultural identity of the Orang Asli. Such a strategy promotes a supportive educational environment, enabling more effective solutions to educational challenges.